IMPLIKASI AKUNTANSI SYARIAH DAN ASURANSI SYARIAH DALAM LEMBAGA KEUANGAN SYARIAH - Djoko Kristianto . (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract Insurance is an agreement, by which a underwriter bind itself to the insured by accepting an premium, to give anti to it because a[n loss of damage or advantage which is in hope,yang possibly will in its distress because an event which is not certain, or to give an payment based by to the dying or its life is underwritten someone. Accounting Principles Board statement define the the following accountancy: Accountancy is a service activity, what its function give the quantitative information, generally in size measure money, hitting an economic body of ang meant to be used in decision making of economics used in chosening among some alternative. congeniality Akuntansi of above representing congeniality conventionally, while accountancy of moslem law represent the accountancy which is based on principles of moslem law which its esensi base represent a effort for the contruction of modern accountancy into form which humanist and loaded assess. "Therefore, effort to look for the accountancy form which have face to humanist, emansipatoris, trasendental, and teologikal represent the effort which undoubtedly”. Keywords: moslem law accountancy, moslem law insurance, financial institution moslem law